Clinical and epidemiological aspects in equine aural plaques - Rodrigues, Gabryele Gomidy; Alves, Dara Santos; Bromberger, Cristiana Raach [UNESP]; Nomelini, Quintiliano Siqueira Schroden; Borges, Alexandre Secorun [UNESP]; de Oliveira-Filho, José Paes [UNESP]; Delfiol, Diego José Zanzarini (Springer Nature, 2025)
The association between aural plaques, Equus caballus papillomavirus (EcPV), and the different breeds of horses and risk factors is poorly described. The objective of this study was to determine the clinical prevalence of aural plaques in Mangalarga Marchador (MM) and Quarter Horse (QH) horses in Brazil, to evaluate the association of this prevalence with some risk factors, and to detect the presence of EcPV DNA (types 1–10) in aural plaques biopsies. A total of 400 MM and 425 QH horses, were clinically evaluated. For each horse, an identification form was completed, containing information on breeding, sex, age, presence, and classification of aural plaque lesions, presence of ectoparasites, management type, ear clipping performed, and sensitivity to ear palpation. Biopsies of the lesions were taken from 30 horses and assessed for the presence of EcPV DNA using PCR. Among the MM and QH horses evaluated, 41.5% and 33.6%, respectively, had aural plaques. The MM horses showed a higher frequency of plaques than QH (p = 0.02). At least one viral type was identified in 90% of all aural plaque biopsies, with EcPV4 being the most frequently detected in both breeds, followed by EcPV6, EcVP5, EcVP3 and EcPV1 respectively. In one sample, EcPV1 was detected alone, although it had previously been described only in copresence. The copresence of viral DNA the MM 73% (11/15) QH 27% (4/15) horses. Aural plaques are widely distributed, with a higher prevalence of EcPV4. Additionally, MM horses have higher susceptibility and frequency of the disease than QH horses.
Keywords: Dermatology; Horse; Mangalarga Marchador; Papillomavirus; Quarter horse